Adaptive and Probabilistic Power Control Algorithms for RFID Reader Networks. (2008) - Cha Cha, Kainan Kainan; Ramachandran Ramachandran, Anil Anil; Jagannathan Jagannathan, Sarangapani Sarangapani
Abstract : In radio frequency identification (RFID) systems, the detection range and read rates will suffer from interference among high power reading devices. This problem grows severely and degrades system performance in dense RFID networks. Consequently, medium access protocols (MAC) protocols are needed for such networks to assess and provide access to the channel so that tags can be read accurately. In this paper, we investigate a suite of feasible power control schemes to ensure overall coverage area of the system while maintaining a desired read rate. The power control scheme and MAC protocol dynamically adjusts the RFID reader power output in response to the interference level seen during tag reading and acceptable signal-to-noise ratio (SNR). We present novel distributed adaptive power control (DAPC) and probabilistic power control (PPC) as two possible solutions. A suitable back off scheme is also added with DAPC to improve coverage. Both the methodology and implementation of the schemes are presented, simulated, compared, and discussed for further work.